2014
DOI: 10.1177/0950017014542499
|View full text |Cite
|
Sign up to set email alerts
|

The bigger the worse? A comparative study of the welfare state and employment commitment

Abstract: This article investigates how welfare generosity and active labour market policies relate to employment commitment. As social policy is increasingly directed towards stimulating employment in broader sections of society, this article particularly studies employment commitment among groups with traditionally weaker bonds to the labour market. This is also theoretically interesting because the employment commitment in these groups may be more affected by the welfare context than is the employment commitment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Secondly, the positive effects of regular voluntary work on mental health and well-being can be maximized with generous unemployment benefits. Concerns that regular volunteering and generous unemployment benefits may result in the so-called 'lock-in effect' (Røed and Raaum, 2006), by discouraging the unemployed from searching for paid work in the labour market, may be unfounded given that Van der Wel and Halvorsen (2015) found that welfare generosity is not detrimental to employment commitment and motivation to work. Furthermore, if voluntary work does improve mental health, then it has the potential to increase the capability of someone who is unemployed to find a paid job.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the positive effects of regular voluntary work on mental health and well-being can be maximized with generous unemployment benefits. Concerns that regular volunteering and generous unemployment benefits may result in the so-called 'lock-in effect' (Røed and Raaum, 2006), by discouraging the unemployed from searching for paid work in the labour market, may be unfounded given that Van der Wel and Halvorsen (2015) found that welfare generosity is not detrimental to employment commitment and motivation to work. Furthermore, if voluntary work does improve mental health, then it has the potential to increase the capability of someone who is unemployed to find a paid job.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike sanctions, none of the aforementioned studies has considered the impact on job quality. The overall positive impact on employment is confirmed by the comparative analysis provided by Van der Wel and Halvorsen (2015) who reveal a positive relation between employment engagement and activation-oriented social spending.…”
Section: Empirical Literature On Activation Programmesmentioning
confidence: 62%
“…Norway is a generous and comprehensive welfare state and has an active labour market policy. Welfare states with a resource perspective like this, might affect norms and values [30]. The latent functions of work like having colleagues, social support, the achievements of personal goals, time structure and quality of life might be considered as potentially more important motivators for whether people want a job or not.…”
Section: Discussionmentioning
confidence: 99%